Analysis of Occupancy Rates at Hotel Wisata Palu - Ni Wayan Ayu Sutari; Haris Abd Kadir; Abdul Rahman (International Journal of Health, Economics, and Social Sciences (IJHESS), 2020)
This study aims: is to determine the occupancy rate at Hotel Wisata Palu, which causes it to survive the immense competition in the hotel business sector in Palu City. In 2019, the room occupancy rate increased, with the deluxe premium room type, the number of rooms sold in 2019 amounting to 159 rooms with an occupancy value of 79.5. Only room types, the number of rooms sold in 2019, is 216 rooms with an occupancy value of 15.43. The number of superior rooms sold in 2019 is 945 rooms with an occupancy value of 236.26. Standard room types, the number of rooms sold in 2019 amounted to 1,085 rooms with an occupancy value of 180.83. Hotel Wisata Palu management maintains occupancy rates and understands market demands supported by a good marketing strategy. Hotel Wisata Palu, as a service company, can implement a service marketing strategy and see the realities of business in Palu City